2021
DOI: 10.3390/agriculture11121246
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Enhanced Growth and Biological Nitrogen Fixation of Wild Soybean (Glycine max subsp. soja Siebold & Zucc.) in a Coastal Soil of China

Abstract: The high salinity and nutrient deficiency in degraded coastal soil restricts crop growth and grain production. The development of effective and novel technology for coastal soil remediation is of great requirement. The effect of wood waste biochar (WB) on the growth and biological nitrogen fixation of wild soybean (Glycine max subsp. soja Siebold & Zucc.), a legume with high economic values and salt tolerance in coastal soil, were explored using a 42-day pot experiment. With the optimal rate of WB addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
(77 reference statements)
0
4
0
1
Order By: Relevance
“…In group II, Arthrobacter , Bradyhizobium , Devosia , Pseudarthrobacter , Pseudolabrys , and Nitrospira in the center of the network proved to play an important part in the nitrogen cycle ( Figure 7 b). Members in Pseudarthrobacter showed a positive correlation with the content of available nitrogen in various agricultural ecological soil systems, confirming that Pseudarthrobacter could promote crop growth by nitrogen fixation [ 62 , 63 ]. Based on the genome data, Buckley [ 64 ] indicated that Pseudarthrobacter and Arthrobacter were able to reduce nitrate to nitrite.…”
Section: Discussionmentioning
confidence: 95%
“…In group II, Arthrobacter , Bradyhizobium , Devosia , Pseudarthrobacter , Pseudolabrys , and Nitrospira in the center of the network proved to play an important part in the nitrogen cycle ( Figure 7 b). Members in Pseudarthrobacter showed a positive correlation with the content of available nitrogen in various agricultural ecological soil systems, confirming that Pseudarthrobacter could promote crop growth by nitrogen fixation [ 62 , 63 ]. Based on the genome data, Buckley [ 64 ] indicated that Pseudarthrobacter and Arthrobacter were able to reduce nitrate to nitrite.…”
Section: Discussionmentioning
confidence: 95%
“…В нашем исследовании при внесении биоугля происходило достоверное увеличение содержания общего азота в почве в конце эксперимента. Это может быть связано с тем, что внесение биоугля часто приводит к изменению структуры бактериального сообщества, что сопровождается уменьшением выщелачивания азота и увеличением азотфиксирующей активности [19][20][21]. В связи с этим внесение биоугля должно улучшать азотное питание растений, однако в проведенном эксперименте произошло достоверное снижение массы растений и зерновок.…”
Section: обсуждение и выводы (Discussion and Conclusion)unclassified
“…Accordingly, the drought and salinity stress tolerance of soybean and rice plants could be significantly improved by the amendment of biochar [122,123]. However, a threshold level of biochar supply was evident [124]. In this case, if the concentration of biochar exceeds this limit, the ion binding capacity in the soil fraction is too high.…”
Section: Improving Soil Quality By the Addition Of Biocharmentioning
confidence: 99%
“…Additional recent research indicated that the positive effect of biochar is not restricted to the water and nutrient supply to plant roots, but extends to soil microorganisms, as well [121,126]. The beneficial effect of soil inoculation with plant growth promoting bacteria was enhanced by the parallel application of biochar [124]. When measuring the stress-induced inhibition of physiological and biochemical traits, the beneficial effects of biochar and plant growth promoting bacteria were added with all of the tested plant species [127].…”
Section: Improving Soil Quality By the Addition Of Biocharmentioning
confidence: 99%